Sophie's Sacrifice To Find A True Love Reflected In Letters ToJuliet Movie (2010): An Individual Psychological Approach - Saraswati, Utami; , Drs. H. Abdillah Nugroho, M. Hum; , Titis Styabudi. SS. M. Hum (2013)
In analysis, the writer uses qualitative method. The object of the study is Letters to Juliet written by Gary Winick. The outcome of the study is shown in the following conclusions. First, there is a relationship between Letters to Juliet and an individual psychology, particularly in human striving for superiority and the creativity of human to support their strives. Letters to Juliet is a movie where the story tells about the existence of Juliet Capulet. The climax on action appears from both couple with a different ways of purposes. Second Letters to Juliet is analyzed by using individual psychological approach where there are six elements as the point. The six elements consist of striving for superiority, inferiority feeling, fictional finalism, style of life, creative self and social interest. Sophie, the major character tries to become an honest woman to get her future better because her finalism is that, on her entire life, Sophie needs love. Her dream is to get someone she loves who cares of her and knows her better rather than knowing about himself. To get her fictional finalism, Sophia must face the obstacle of life. The obstacle that creates her inferiority is that Sophie feels anxious when she knows that her fiancé only loves with his hobby and his dreams as a chef of a restaurant. The creative of Sophia helps her to run her life. Her creativity such as after he is separated with her fiancé, she feels lonely because there is no one can give her love and attention. Her style of life supports her social life everyday.